A Model of Development Maritime Tourism Competitiveness in Nikoi Island, Riau Islands Province - I Dewa Gde Sugihamretha (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
This study aims to explain the factors and models to develop the competitiveness of marine tourism destinations in Nikoi Island, Bintan Regency, Riau Islands Province by using a qualitative approach (descriptive method). Data and information were generated through in-depth interviews, Focus Group Discussion (FGD), and literature studies which were then analyzed using the Porter Value Chain framework (1985). The richness and uniqueness of natural resources that can offer beauty and experience for travelers are basic capital for the development of marine tourism in Nikoi Island. Investors play a central role which starts from planning, construction design to management and continuous business improvement. A large percentage of Bintan’s PAD comes from their tourism sector which includes Nikoi island. The development of Nikoi Island as a tourist destination can be used as a model to develop inclusive and sustainable marine tourism in thousands of other small islands owned by Indonesia with private sector acting as the main investor. However, during implementation in the field, the private sector cannot stand alone. They must be able to cooperate with the Government (both at Central and Regional level) and other related stakeholders. In the national midterm plan, 2020 – 2024, the development of tourism in small islands can be seen as a breakthrough that forms new economic growth centers.